REFERENCES OF DISCOURSE AND ITS TYPES IN AKSHATA MURTHY: UK™S FIRST LADY SPEECH - Manurung, Siti Tasya Jelita (Universitas Negeri Medan, 2023)
This study examined the references used in Akshata Murthy's speech